Analysis of open-pit coal mine collapse accident based on AcciMap model - Zhaobo CHEN; Yang LI; Yamin GUO (Meikuang Anquan)
Take Alxa open-pit coal mine collapse accident on February 22 in Inner Mongolia as an example, on the basis of identifying the cause factors of the accident, the logical relationship between the cause factors of the accident is sorted out, and the AcciMap model of the “2·22” accident is constructed; UCINET was used to analyze the key cause factors and causal chain of the accident; the prevention and control measures of open-pit coal mine collapse accident are proposed. The results show that the key factors leading to the accident are inadequate safety supervision, lax law enforcement inspection, illegal provision of technical services, illegal organization of production and cross-border mining, mere formality of safety management, frequent blasting and high-intensity stripping mining. Poor safety development concept→poor implementation of safety inspection work→inadequate safety supervision→illegal organization of production and cross-border mining→frequent blasting and high-intensity stripping mining→edge rock slide and collapse is the key causal chain of the accident.